Predictors of prolonged grief in an internet-based grief therapy for people bereaved by suicide. (May 2022) - Schmidt, Viktoria; Treml, Julia; Linde, Katja; Peterhänsel, Carolin; Kersting, Anette
Abstract: Internet-based cognitive-behavioural grief therapy (ICBGT) has proven to be effective for people bereaved by suicide, however the extent to which patients can benefit from therapy seems to differ. This study investigates predictors of initial grief as well as change in grief severity following treatment in an ICBGT for people bereaved by suicide. Data was gathered from a randomized control trial including 57 people participating in a 5-week intervention. Change in grief symptoms was calculated using absolute change scores of grief. In order to examine best overall combination of independent variables, best subset regressions were conducted. Higher levels of pre-test grief were associated with worse sleep quality (β = 0.32, p  = .002), lower self-esteem (β = −0.37, p  = .002), lower support seeking (β = −0.38, p  = .006), and a higher need for social support (β = 0.28, p  = .028). A greater reduction in grief severity was associated with higher self-efficacy (β = −0.49, p  = .001), higher attachment anxiety (β = −0.31, p  = .017) and higher pre-test grief symptoms (β = −0.39, p  = .006). Attention should be paid to the intensity of grief, the attachment style and a positive self-image, as these variables seem to influence the extent, to which patients' symptoms of PGD subside following ICBGT. To specifically target factors of patients that require improvement, further studies are needed.